MANAGEMENT OF INFRASTRUCTURE DEVELOPMENT IN RUSSIAN REGIONS ON THE BASIS OF PUBLIC-PRIVATE PARTNERSHIP - F. Ibyatov (Вестник университета)
Building a modern, sustainable and reliable infrastructure is crucial to meet the growing needs of people in Russian regions. Investment in infrastructure increases economic growth temps, opens up new economic opportunities and facilitates investment in human capital. Сurrently, the population of the Russian regions is experiencing infrastructure deficit, as evidenced by congested roads, poorly maintained recreational areas, deteriorating social infrastructure assets: schools, hospitals, that are either missing or in urgent need of repair. In this regard, the state bears huge costs in parallel with the reduction of productivity and competitiveness of the regions and observing a lower standard of living. The regional authorities are not able to finance the needs of regional infrastructure, some regions have infrastructure created many years ago, that needs modernization, it is necessary to find funding for «greenfield projects – infrastructure projects implemented in undeveloped «green» areas». The decision of the regional authorities on the implementation of public-private partnership should be based on determining the benefits, which this approach will bring to the public: lower costs, high level of service or reduced risk. The conclusion, that the provision of regions with infrastructure facilities is due to the satisfaction of social needs of citizens, economic well-being and a decent standard of living of the population, – has been substantiated.